EFEKTIVITAS MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA PEMBELAJARAN BAHASA INDONESIA - Suanto; Hastuti, Sri; Asiyah, Dewi (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama'ah, 2024)
This study aimed to analyze the effect of contextual teaching and learning on students' learning outcomes in Indonesian language class IV. This type of research was an experimental research of one group pretest-posttest design with the research sample, namely all fourth grade students with contextual teaching and learning learning model. Based on the results of research and data analysis, it can be seen from the average posttest value obtained from student learning achievement after applying the contextual teaching and learning learning model. The average value of the pretest before using the contextual teaching and learning learning model was 61.25. After using the contextual teaching and learning learning model, the average value was 76.66. So that the results of the prettest and posttest values can be concluded that the posttest value is greater than the prettest, so the contextual teaching and learning learning model has an effect in improving the learning outcomes of grade IV students in Indonesian language learning.